2017
DOI: 10.1016/j.quascirev.2017.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between fluvial evolution and karstification related to climatic, tectonic and eustatic forcing in temperate regions

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 99 publications
(191 reference statements)
1
18
0
1
Order By: Relevance
“…Many studies have related the genesis of relict cave levels and their subsequent abandonment to base‐level dynamics, driven by river incision in fluvial valleys or sea‐level oscillations in coastal areas (Plan et al ., 2009; Piccini and Landelli, 2011; Audra and Palmer, 2013; Calvet et al ., 2015; Columbu et al ., 2015; Nehme et al ., 2016; Pennos et al ., 2016; Harmand et al ., 2017; Bella et al ., 2019). The rate of river incision is influenced by several variables.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have related the genesis of relict cave levels and their subsequent abandonment to base‐level dynamics, driven by river incision in fluvial valleys or sea‐level oscillations in coastal areas (Plan et al ., 2009; Piccini and Landelli, 2011; Audra and Palmer, 2013; Calvet et al ., 2015; Columbu et al ., 2015; Nehme et al ., 2016; Pennos et al ., 2016; Harmand et al ., 2017; Bella et al ., 2019). The rate of river incision is influenced by several variables.…”
Section: Introductionmentioning
confidence: 99%
“…In high‐latitude areas where periglacial/glacial processes are the dominant influence on Quaternary valley incision, climatically forced incision and aggradation (Aranburu et al ., 2014) influences the development of cave levels. Each phase of fluvial incision and base‐level fall increased the hydraulic gradient in the chalk aquifer, causing a reorganization of the conduit system (Harmand et al ., 2017). These respond to base‐level fall by the development of new phreatic conduits graded to the lower base level, and/or by vadose incision of the existing passage.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, few evidences for tectonic control of fluvial sedimentation can be found (Allen, Fielding, Rygel, & Gibling, 2013;Harmand et al, 2017). In contrast, climatic variations have undoubtedly been significant in influencing on stratigraphic architectural in many continental settings (Gibling, Fielding, & Sinha, 2011;Maccarrick & Loeys, 2005;Maddy, 2002;Weissmann, Mount, & Fogg, 2002), especially in the evolution of sedimentation in the Junggar Basin in varying degrees (Khadkikar et al, 1999;Mader & Redfern, 2011;Vandenberghe, 2003).…”
Section: Response Of Evolution Of Braided-meandering System To Climatementioning
confidence: 57%
“…In general, the telogenetic karst environment could vertically be subdivided into an epikarstic, vadose, and phreatic zone (Harmand et al, ). This is also the case for the Majiagou Formation in the Jingxi area, which is evidenced by petrographic analyses.…”
Section: Discussionmentioning
confidence: 99%